Household Solar Photovoltaic Adoption in the Maldives: A Socioeconomic Perspective - Fathimah, Rukshana; Darsono, Susilo Nur Aji Cokro; Suphanchaimat, Nongluck (Jurnal Ekonomi & Studi Pembangunan, 2020)
Energy has become an essential part of our lives, but the current energy sources we used are depleting and non-renewable. In the case of Maldives, fuel energy is expensive due to importation and high transportation cost.Â  Besides, Atoll islands' characteristics require each island to have a power plant using fossil fuel, and the fuel storage availability is limited, making the electricity in these islands unstable and costly. Therefore, the need for cleaner and reliable resources for energy is essential in order to ensure a better future.Â  This study aimed to determine the factors influencing solar energy acceptance by inviting people to participate in the electronic survey in the Maldives, with 119 samples collected. The result revealed that most respondents were willing to go for a solar energy source for electrification due to the current high electricity bills. A binary logistic regression analysis was performed to predict the factors for the acceptance of solar energy. The result showed that people's attitudes and current electricity bills were significantly influential in solar energy acceptance. The presumptions for policymakers are to increase the people's knowledge and awareness to elevate a positive attitude and involve the private sector to increase competition and utility in the field